Termosurgical technology and equipment on prosthetics in implants for the elderly people - Ponomarenko, Victor; Kamalov, Rafik; Khudetskyy, Igor (Видавництво Львівської політехніки, 2012)
The report presents the results of experimental studies that focus on features of prosthetic implants in the elderly.
Keywords: Dental implant; Orthopedics construction; dental termosurgical technology